EFFICIENT MANAGEMENT OF RESOURCE UTILIZATION IN CASSAVA PRODUCTION IN A FRIENDLY POLICY ENVIRONMENT: IMPLICATIONS FOR CASSAVA PRODUCTION IN NIGERIA - Asogwa, Benjamin C.; Umeh, Joseph C.; Penda, Simon T. (European Scientific Journal, ESJ, 2012)
This study examined efficient farm management in a friendly policy environment and its implications for agricultural production in Nigeria using the cassava industry as a case study. Data were collected from randomly sampled 360 cassava farmers in Benue State. In-depth analysis of data collected was done using the stochastic frontier production function model. The result of the stochastic frontier production model indicated that government policy which favoured increased input use in cassava production in Nigeria resulted to more than proportionate increase in cassava output in Nigeria. The policy packages on cassava resulted to efficient utilization of production resources in cassava production in Nigeria, and hence profit maximization by the farmers. Technical efficiency in cassava production in Nigeria could be increased by 24% through better use of available resources given the current state of technology – via farmer-specific factors, which included access to improved cassava varieties, access to improved cassava processing technology, access to available cassava markets, access to improved extension services and agricultural credits. Moreover, 98% of the variations in input among the farms were due to differences in technical efficiency occasioned by differences in the relative access of cassava farmers to the cassava policy packages.